ANALISA PERPINDAHAN PANAS HEAT EXCHANGER MESIN INDUK (STUDI KASUS: KM. SUMBER MUTIARA) - Rizqi Ilmal Yaqin; Miftahul Huda; Mula Tumpu; Yuniar Endri Priharanto; Juniawan Preston Siahaan; Bobby Demeianto; Bambang Hari Priyambodo; Mega Lazuardi Umar (P3M Politeknik Negeri Indramayu, 2022)
Heat exchanger (HE) is a component of the main engine cooling system that plays a very important role in the process of changing the fluid temperature by exchanging the amount of heat with other fluids. The use of HE in the main engine cooling system should be considered in controlling after operation. HE performance can be analyzed using heat transfer analysis in the form of heat absorbed by HE (Q), LMTD and heat transfer coefficient (U). This study aims to analyze heat transfer in the form of calculations of absorbed heat, LMTD and heat transfer coefficient on the main engine HE KM Sumber Mutiara. This study measures the temperatures of fresh water and sea water entering and leaving the HE. In addition, measurement of water discharge and determination of the dimensions of the HE used for the main engine cooling system of KM Sumber Mutiara. This research shows that the highest heat value absorbed by HE (Q) is at RPM 1200 at 44.85 kJ/s, for the LMTD value at RPM 1000 at 45.69 oC and for the U value at RPM 1100 at 824 W/m2. oC. HE main engine KM Sumber Mutiara has not maximized its performance due to the fouling factor from sea water. The need for preventive maintenance and additional filters on the KM Sumber Mutiara Main Machine Heat Exchanger to increase the effectiveness of the HE.